2012
DOI: 10.1016/s0972-6292(16)30501-0
|View full text |Cite
|
Sign up to set email alerts
|

Is the Measurement of Accessory Pathway Refractory Period Reproducible?

Abstract: IntroductionShort accessory pathway (AP) effective refractory period (ERP) is one of the risk factors in Wolff-Parkinson-White syndrome (WPW). The purpose of study was to evaluate the reproducibility of APERP measurement during a same electrophysiological study (EPS).MethodsEPS consisted of 2 APERP measurements performed prospectively in 77 patients for a WPW in control state (CS) at a cycle length of 400 ms (n=76) and after isoproterenol (n=56).ResultsIn CS, 18 patients (24 %) had the same APERP at both measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…We observed 31 patients (27.90%) with an AP refractory period ≤ 240 ms, which has been recognized as a risk marker of sudden death in patients with WPW syndrome. 18,19 The APs evaluated in the study showed an ability to conduct the stimulus in both anterograde and retrograde directions in most individuals of both sexes (60 men [54.10%] and 39 women [35.10%]), with no significant differences between sexes (p > 0.05 ). The EPS also revealed that only eight individuals (7.20%) had an intermittent WPW pattern, with no significant differences in the type of WPW pattern by sex (p > 0.05).…”
Section: Resultsmentioning
confidence: 80%
“…We observed 31 patients (27.90%) with an AP refractory period ≤ 240 ms, which has been recognized as a risk marker of sudden death in patients with WPW syndrome. 18,19 The APs evaluated in the study showed an ability to conduct the stimulus in both anterograde and retrograde directions in most individuals of both sexes (60 men [54.10%] and 39 women [35.10%]), with no significant differences between sexes (p > 0.05 ). The EPS also revealed that only eight individuals (7.20%) had an intermittent WPW pattern, with no significant differences in the type of WPW pattern by sex (p > 0.05).…”
Section: Resultsmentioning
confidence: 80%
“…In fact, in the PACES/HRS 2012 Management of Asymptomatic Preexcitation Recommendations, it was recommended that in the absence of inducible atrial fibrillation, the minimal cycle length of preexcitation should be used as an alternative . However, in our opinion the minimal cycle length of preexcitation is variable in absence of sedation mainly in children …”
Section: Limitationsmentioning
confidence: 73%
“…For starters, there is clear evidence that the measured accessory pathway refractory period is not consistently reproducible from one measured time to another; in fact, the reproducibility is even worse on isoproterenol. 28 Choosing a combined accessory pathway effective refractory period and minimal pre-excited cycle length during atrial incremental pacing ⩽250 ms likely increases the specificity, but may reduce the sensitivity of detecting a high-risk accessory pathway. Furthermore, the accessory pathway effective refractory period as an isolated variable is of little prognostic value for the risk of syncope, atrial fibrillation, or atrioventricular reciprocating tachycardia and is less well correlated than the SPERRI in atrial fibrillation; 9,29,30 nonetheless, the authors of these two studies showed that 5% of patients with intermittent pre-excitation may have a high-risk accessory pathway at the time of an invasive electrophysiology study, and if isoproterenol is utilised up to 11% may have pathways deemed high risk.…”
Section: Value Of Exercise Stress Testing In the Asymptomatic Patientmentioning
confidence: 99%
“…, 27 Although neither retrospective study was intended a priori to be an assessment of risk stratification, both groups used similar definitions of high risk: an accessory pathway effective refractory period or minimal pre-excited cycle length during incremental atrial pacing ⩽250 ms. From a purely electrophysiological standpoint, accessory pathway effective refractory period is different than a measured SPERRI or minimal pre-excited cycle length during atrial incremental pacing. For starters, there is clear evidence that the measured accessory pathway refractory period is not consistently reproducible from one measured time to another; in fact, the reproducibility is even worse on isoproterenol 28 . Choosing a combined accessory pathway effective refractory period and minimal pre-excited cycle length during atrial incremental pacing ⩽250 ms likely increases the specificity, but may reduce the sensitivity of detecting a high-risk accessory pathway.…”
Section: Approaching the Asymptomatic Patient With Intermittent Pre-ementioning
confidence: 99%